Acute Appendicitis Complicated by Pylephlebitis: A Case Report. (7th November 2013) - Castro, Ricardo; Fernandes, Teresa; Oliveira, Maria I.; Castro, Miguel
Abstract : Pylephlebitis is defined as septic thrombophlebitis of the portal vein. It is a rare but serious complication of an intraabdominal infection, more commonly diverticulitis and appendicitis. It has an unspecific clinical presentation and the diagnosis is difficult. The authors report a case of a 21-year-old man with acute appendicitis complicated by pylephlebitis. The diagnosis was made with contrast enhanced CT.